Exploring Employers’ Insights on Graduate Employability and Work Readiness in the Age of Artificial Intelligence - Ahmad Tajuddin, Siti Nor Amalina; Ali, Abdul Halim (Persepsi: Communication Journal, 2025)
This study aims to explore Malaysian employers’ insights regarding the graduate employability and work readiness of young university graduates, exploring how employability skills required by employers can be aligned with the skills taught at the university level. Moreover, the objective of this study was to examine the insight provided by employers regarding the readiness of young graduates for the workforce in Malaysia. Through a qualitative method, the data was gathered by conducting in-depth interviews with 23 employers in high-level management positions within both public and private organizations. The findings revealed that universities serve as a place where students can refine their cognitive abilities and enhance crucial skills such as communication, critical thinking, leadership, character development, and creativity. Although university graduates are not yet considered work-ready, universities have started revising courses and programs that link to practice-based knowledge to meet the industrial demand. These findings carry implications for educational institutions to understand industrial requirements, enabling students to adapt professionally and socially to workplace transformations beyond the campus environment.